Interdisciplinary sport injury research and the integration of qualitative and quantitative data - S.E Hausken-Sutter; K Boije af Gennäs; A Schubring; S Grau; J Jungmalm; N Barker-Ruchti (BMC Medical Research Methodology, 2023)
Abstract Background To understand and prevent sport injuries, scholars have employed different scientific approaches and research methods. Traditionally, this research has been monodisciplinary, relying on one subdiscipline of sport science and applying qualitative or quantitative research methods. Recently, scholars have argued that traditional approaches fail to address contextual components of sport and the nonlinear interactions between different aspects in and around the athlete, and, as a way forward, called for alternative approaches to sport injury research. Discussion of alternative approaches are today taking place, however, practical examples that demonstrate what such approaches entails are rare. Therefore, the purpose of this paper is to draw on an interdisciplinary research approach to (1) outline an interdisciplinary case analysis procedure (ICAP); and (2) provide an example for future interdisciplinary sport injury research. Methods We adopt an established definition and application of interdisciplinary research to develop and pilot the ICAP for interdisciplinary sport injury teams aiming to integrate qualitative and quantitative sport injury data. The development and piloting of ICAP was possible by drawing on work conducted in the interdisciplinary research project “Injury-free children and adolescents: Towards better practice in Swedish football” (the FIT project). Results The ICAP guides interdisciplinary sport injury teams through three stages: 1. Create a more comprehensive understanding of sport injury aetiology by drawing on existing knowledge from multiple scientific perspectives; 2. Collate analysed qualitative and quantitative sport injury data into a multilevel data catalogue; and 3. Engage in an integrated discussion of the collated data in the interdisciplinary research team. Conclusion The ICAP is a practical example of how an interdisciplinary team of sport injury scholars can approach the complex problem of sport injury aetiology and work to integrate qualitative and quantitative data through three stages. The ICAP is a step towards overcoming the obstacles of integrating qualitative and quantitative methods and data that scholars have identified.